Agricultura Regenerativa en Fruticultura en el Alto Valle de Río Negro y Neuquén - Aguilar, Neuquen Lautaro; Romagnoli, Sergio Osvaldo; Lorenzo, Hugo Ariel; Buda, Vicente Sebastián; Holzmann, Rosa De Lima; Asencio, Vanesa Alejandra; Gutierrez Franco, Alejo Manuel; Villarraza, Ignacio; Aventín, Jeremías (Asociación Argentina de Extensión Rural (AADER), 2025)
Trabajos eje 5: Extensión rural e innovación